2015
DOI: 10.1016/j.abrep.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The association between at-risk gambling and binge drinking in the general Swedish population

Abstract: While the association between problem gambling and alcohol use disorders has been studied previously, little is known about the association between risk gambling and risk drinking. This study aimed at examining the association between at-risk gambling and binge drinking in the general Swedish population and to test whether this association remained after controlling for demographic factors. The data was part of a larger ongoing survey in the general Swedish population. Respondents (N = 19 530) were recruited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Based on the three subquestions one dichotomous overall measure of risk gambling was constructed: Participants who responded at least “1–2 times” to any of the three subquestions were classified as engaging in risk gambling, while those who responded “Never” to all three subquestions (and those who stated that they had not gambled at all in the last 12 months) were classified as not engaging in risk gambling. A previous study using this definition of risk gambling revealed a prevalence rate of 3.5% (Brolin Låftman, Alm, Olsson, Sundqvist, & Wennberg, 2019), which is in line with other studies on risk gambling in Sweden (Sundqvist, Rosendahl, & Wennberg, 2015). In order to validate the measure, internal consistency of the set of items (Cronbach's α = 0.66) was examined and exploratory factor analysis (EFA) was conducted.…”
Section: Methodssupporting
confidence: 91%
“…Based on the three subquestions one dichotomous overall measure of risk gambling was constructed: Participants who responded at least “1–2 times” to any of the three subquestions were classified as engaging in risk gambling, while those who responded “Never” to all three subquestions (and those who stated that they had not gambled at all in the last 12 months) were classified as not engaging in risk gambling. A previous study using this definition of risk gambling revealed a prevalence rate of 3.5% (Brolin Låftman, Alm, Olsson, Sundqvist, & Wennberg, 2019), which is in line with other studies on risk gambling in Sweden (Sundqvist, Rosendahl, & Wennberg, 2015). In order to validate the measure, internal consistency of the set of items (Cronbach's α = 0.66) was examined and exploratory factor analysis (EFA) was conducted.…”
Section: Methodssupporting
confidence: 91%
“…The prevalence of risk gambling according to this definition is about 3.5 percent and in line with other Swedish studies (e.g. Sundqvist, Rosendahl, & Wennberg, 2015).…”
Section: Risk Gamblingsupporting
confidence: 92%
“…However, studies from the pathological gambling literature have already shown that electronic harm-reduction messages are optimally effective "in the moment" when messages create an interruption in play and require active removal by the player (Ginley et al, 2017). Both at-risk gambling and binge drinking feature episodic escalations in an addictive behavior (Sundqvist et al, 2015); thus, in-the-moment interventions might improve both conditions. We propose that, if BDs' concurrent use of alcohol and social media could be leveraged to inform the optimal timing and content of EMIs, then individually tailored harm-reduction messages delivered via social media while BDs are only moderately consuming alcohol (i.e., before signifi cant impairment) might be useful in preventing an episode of social drinking from escalating into a binge.…”
Section: Discussionmentioning
confidence: 99%